IN VITRO REPROGRAMMING OF NITRIC OXIDE-SYNTHETIC MECHANISMS FOR M1 AND M2 PHENOTYPES OF MURINE PERITONEAL MACROPHAGES: DEPENDENCE ON DIFFERENT SERUM CONCENTRATIONS - S. V. Kruglov; S. V. Lyamina; T. Yu. Vedenikin; O. A. Borodovizyna; I. A. Suvorova; Sh. L. Shimshelashvili; I. Yu. Malyshev (Медицинская иммунология, 2014)
Abstract. Macrophages are among key players of inflammatory events, acquiring either pro-inflammatory M1, or anti-inflammatory M2 phenotype, dependent on their microenvironment. Some endogenous macrophagereprogramming factors (MRFs), e.g., TGF-β (an M2-inducing agent), are found in blood serum. This work confirms a hypothesis on in vitro M1-to-M2 phenotype reprogramming of cultured macrophages, by means of decrease or increase in serum concentration. Noteworthy, the macrophages from C57BL/6 и BALB/c mice strains did not differ with their reprogramming capacity. In general, our results allow of extending present knowledge about a role of environmental factors in regulation of macrophage activities.